Predicting Fertile Oestrus On The Basis Of Plasma Progesterone and Some Metabolites in Buffaloes - SHARMA, H C; DHAMI, A J; KAVANI, F S; KILLEDAR, ANKITA (The Indian Journal of Animal Reproduction, 2023)
A study on 225 normal cyclic buffaloes revealed that the plasma progesterone concentration at fertileoestrus was significantly (P < 0.0 I) lower than the infertile oestrus (0.26 ± 0.02 vs 0.97 ± 0.13 ng/ml).Pregnancy occurred only in animals having basal progesterone level (< 0.3 ng/ml) at Al. The mean values ofplasma glucose, total protein and total cholesterol concentration observed at oestrus in buffaloes were 57.65 ±0.52 mg/di, 7.92 ± 0.07 g/dl and 113.75 ± 2.82 mg/di, respectively. The levels neither varied significantlybetween fertile and infe1tile oestruses nor between village centres, though the plasma total cholesterol was low atfertile oestrus.
Keywords: Buffalo; Fertile oestrus; Plasma progesterone; Metabolites; Fertility